Implementasi Peraturan Gubernur Tentang Tunjangan Tambahan Penghasilan Pegawai Negeri Sipil Dan Calon Pegawai Negeri Sipil di Lingkungan Sekretariat Dprd Provinsi Sumatera Utara - Lubis, Kartini; Kadir, Abdul; Harahap, Dumasari (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
The formulation of the problem in this study are how is the implementation of North Sumatra Governor Regulation Number 18 Year 2018 concerning Additional Income Allowances for Civil Servants and Prospective Civil Servants in the North Sumatra Provincial Government, what factors are obstacles in realizing improved performance and discipline of Civil Servants in the North Sumatra Provincial DPRD Secretariat, with the aim of research: 1) to find out and analyze the implementation of North Sumatra Governor Regulation Number 18 Year 2018 regarding Income Allowances for Civil Servants and Prospective Civil Servants in the Government of North Sumatra Province , 2) to find out what factors are obstacles in realizing improved performance and discipline of Civil Servants in the North Sumatra Provincial DPRD Secretariat. The research method used is descriptive method, while the data analysis technique uses qualitative descriptive. From the results of this study indicate that the implementation of Governor Regulation No. 18 of 2018 concerning Income Allowance for Civil Servants and Prospective Civil Servants has not been fully successful in the North Sumatra Provincial DPRD Secretariat. Implementation has been successfully implemented in terms of communication and bureaucratic structure, but has not been successfully implemented in terms of resources and dispositions. Constraints faced in realizing improved performance and discipline of civil servants within the North Sumatra Provincial DPRD Secretariat are appraisal officials (superiors) unable to control the views of personal relations in evaluating subordinates' work, TTP payments often cannot be done in a timely manner because funds are not yet available, disciplinary sanctions are still relatively indecisive, and employees often report excessively. It is recommended that supervisors as appraisal officials need to eliminate the influence of the element of closeness in making judgments on the performance of subordinates, and be assertive in giving sanctions to employees who subscribe to disciplinary regulations